Outcomes of Trauma during Pregnancy in Hail City - Saudi Arabia - Al-Shammari, Tahani M.; Alshammari, Rawaby K.; Al-Shammari, Nouf M.; Alfouzan, Rawan k.; Alshammari, Shuaa S.; Alshammery, Wudian; Alshammari, Shroog K.; AlTbenawi, Areeb M.; Parveen, Nuzhat (Arab Journal for Sciences and Research Publishing, 2016)
Aim: To identify causes of trauma in pregnancy and it's outcomes over mother and fetus.Methodology: A cross-sectional study was  conducted Hail City that involved  830 pregnant  women from 2010 to 2015. By using a convenience sampling method a 830 pregnant women in Hail city in the KSA who are 18 to 45 years of age were involved in this study. Data were collected by a paper-based questionnaire and internet-based survey. Results: Traumatized women during pregnancy were 336 (40.5%) of 830 pregnant women involved (SD = 1.8, SE = 0.10038, Mean = 2.6071), and there were 218 (64.9%) got living births, while 118 (35.1%) their babies died. Many causes of trauma like falling and sliding 41.4%,  carrying heavy load 21,9%, motor vehicle crashes 11.1%, diseases 10.4%, domestic violence 4.5% and other 9.8%.Conclusion: Falling and sliding women during pregnancy are the most common cause of trauma followed by carrying heavy loads, motor vehicle crashes, diseases, and domestic violence, that associated with fetal birth defect or death.
Keywords: Pregnancy; trauma; Hail city; outcomes; Saudi Arabia